2019
DOI: 10.2139/ssrn.3334076
|View full text |Cite
|
Sign up to set email alerts
|

Hot Spots Policing in a High Crime Environment: An Experimental Evaluation in Medellín

Abstract: Objectives: Test direct, spillover and aggregate effects of hot spots policing on crime in a high crime environment. Methods: We identified 967 hot spot street segments and randomly assigned 384 to a six-months increase in police patrols. To account for the complications resulting from a large experimental sample in a dense network of streets, we use randomization inference for hypothesis testing. We also use non-experimental streets to test for spillovers onto non-hot spots, and examine aggregate effects city… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…(1) measurable police presence. Suitable studies reported police presence in quantitative measures, e.g., time of police presence, number of visits, hours of officers per police beat, or length of patrol shifts (e.g., Bowers and Hirsch 1987, Kaplan et al 2000, McGarrell et al 2001, Zech et al 2005, Ratcliffe et al 2011, Taylor et al 2011, Novak et al 2016, Stephensen 2017, Ariel et al 2019, Collazos et al 2020. This excluded studies that either focused on police expenditures (McPheters and Stronge 1974), police personnel (Levine 1975, Levitt 2002, or tried to infer a level of police presence from law enforcement actions such as arrests rates (Weisburd et al 2016).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…(1) measurable police presence. Suitable studies reported police presence in quantitative measures, e.g., time of police presence, number of visits, hours of officers per police beat, or length of patrol shifts (e.g., Bowers and Hirsch 1987, Kaplan et al 2000, McGarrell et al 2001, Zech et al 2005, Ratcliffe et al 2011, Taylor et al 2011, Novak et al 2016, Stephensen 2017, Ariel et al 2019, Collazos et al 2020. This excluded studies that either focused on police expenditures (McPheters and Stronge 1974), police personnel (Levine 1975, Levitt 2002, or tried to infer a level of police presence from law enforcement actions such as arrests rates (Weisburd et al 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Police action does not just work best when focused on target areas but also when focused on certain types of crime. Police presence has particular strong crime reduction effects on motor vehicle theft (Di Tella and Schargrodsky 2004, Collazos et al 2020, Piza et al 2020, violent crimes (Ratcliffe et al 2011, Taylor et al 2011, Novak et al 2016, and property crime (Andresen and Lau 2014). Similarly, gun related crimes Rogan 1995, Rosenfeld et al 2014) and liquor inflictions (Fitterer et al 2017) experienced substantial reductions.…”
Section: Focused (On) Crime Deterrencementioning
confidence: 99%
See 3 more Smart Citations